2002
DOI: 10.1140/epje/i2001-10088-4
|View full text |Cite
|
Sign up to set email alerts
|

Some relevant parameters affecting the glass transition of supported ultra-thin polymer films

Abstract: We have measured, the thickness dependence of the glass transition temperature T(g)( h), using ellipsometry at variable temperature, for poly(methyl-methacrylate) (PMMA) of various tacticity in confined geometry. We report that several factors significantly affect T(g)( h): i) polymer microstructure (stereoregularity of PMMA) related to local dynamics; ii) interfacial interactions; iii) conformation of the polymer chains. These results raise many fundamental questions on the origin of the thickness-dependent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
170
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(184 citation statements)
references
References 0 publications
12
170
1
1
Order By: Relevance
“…Glass transition temperature is expected to increase slightly with BaTiO 3 content. Variations between glass transition temperature (T g ) of bulk polymer and thin polymer films on a ceramic substrate or polymer nanocomposites with ceramic inclusions have already been observed and reported [20][21][22]. These variations have been attributed to interactions occurring between the polymer and the nanoinclusions or substrate.…”
Section: Resultsmentioning
confidence: 96%
“…Glass transition temperature is expected to increase slightly with BaTiO 3 content. Variations between glass transition temperature (T g ) of bulk polymer and thin polymer films on a ceramic substrate or polymer nanocomposites with ceramic inclusions have already been observed and reported [20][21][22]. These variations have been attributed to interactions occurring between the polymer and the nanoinclusions or substrate.…”
Section: Resultsmentioning
confidence: 96%
“…As already stated the corresponding peak of composite systems in Figure 7a, is formed at slightly lower temperatures and appears not to vary with the filler content. In polymer matrix/ ceramic filler composites variation of glass transition temperature between pure polymer and com- posite systems have been observed and reported [20][21][22]. These variations have been attributed to interactions between polymer matrix/ceramic filler and to the wetting level of inclusions.…”
Section: Figure 1 Depicts Images From Scanning Electronmentioning
confidence: 99%
“…[13][14][15][16] Relatedly, there have been various reports of increases in the glass transition temperature, T g , due to the presence of reinforcing fillers; [17][18][19][20][21][22] however, other investigators found no effect of carbon black, silica, and other particles on T g . 23,24 The effect of nanoconfinement on the polymer dynamics, seen in thin films and porous structures, [25][26][27] may have an influence for layered fillers such as clay platelets. 28,29 An obvious direct consequence of filler is that less material participates in the glass transition, suppressing the changes in the temperature coefficients of the modulus, enthalpy, volume, etc., occurring on heating through T g .…”
Section: Introductionmentioning
confidence: 99%